THE TERRITORY OF UZBEKISTAN AND THE ADMINISTRATIVE DIVISION (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
The Republic of Uzbekistan,a doubly landlocked nation in the heart of Central Asia, boasts a territory of significant geographical and geopolitical importance. Encompassing approximately 448,978 square kilometers, it is characterized by a remarkably diverse topography, which includes vast arid deserts, fertile river valleys, and formidable mountain ranges. This paper provides a comprehensive analysis of the territorial and administrative organization of Uzbekistan, delineating its twelve primary administrative divisions, one autonomous republic, and the capital city. It explores how the nation's physical geography—from the Kyzyl Kum Desert to the Fergana Valley—has historically influenced and continues to shape its economic activities, settlement patterns, and administrative governance. The intricate system of regions (viloyats), districts (tumans), and municipalities forms the backbone of the country's political and administrative machinery, ensuring the implementation of state policies and the delivery of public services across its varied landscape.